Introduction to Implant Prosthodontics A Case-Based Clinical Guide - Kourtis, Stefanos; Lampropoulos, Panagiotis; Polychronakis, Nikolaos (Open textbook library., 2022)
Dental implants have been an established treatment option for partially and completely edentulous patients for decades. In the first years of their clinical use, the theoretical background on osseointegration and implant prosthodontics was covered by textbooks that have been characterized as “classical”, and any further research results were reported in scientific papers. During the years, the continuing introduction of new prosthetic components and treatment options has led to evolution in Implant Prosthodontics. Clinicians are informed on these innovations from research papers but each of them is focused on a specific topic or technique. The purpose of this book is to offer a thorough introduction to current Implant Prosthodontics, combining theory and practice in an easy-to-read manner. In each chapter the needed theoretical background and principles are reported, and the techniques are presented with clinical examples in step-by-step manner. The aim is to guide the dentist in his practice combining the needed knowledge with the clinical application and relevance. For this reason, it can be characterized as “A case-based Clinical Guide”. On the other side, clinicians are always concerned about the stages or steps in each technique and for this reason, emphasis has been given to the detailed description of each case with critical discussion on the selection of each specific treatment option. The content of this book is divided in 9 chapters that cover the whole clinical procedure for an implant restoration, from the presurgical evaluation to the fabrication and delivery. The chapters include the needed diagnostic elements for the treatment planning, the design and fabrication of radiographic and surgical guides, the impression techniques, the use of intra-oral scanning, an overview of cement- and screw retained restorations, the digital workflow in implant restorations and the principles for selection and fabrication of implant overdentures.